A Highly Abundant Lectin Protein in Arabidopsis thaliana Confers Resistance Against Pathogens - Maria prihtamala Omega; Skye Thomas Hall; Peer Schenk; Bostjan Kobe (ANNALES BOGORIENSES, 2008)
Lectins are glycoproteins that recognize and bind  to specific carbohydrates. they are  involved  in a range of biological  functions,  such  as  plant defence,  storage  proteins  seed  germination  and  plant  microbe  interactions. Lectin 3.1  (At3g 15356) is a protein in plant model , Arabidopsis thaliana, that has been shown  to be up-regulated in  all  defence  pathways, especially  in  responce  to methyl  ester jasmonate  (MJ) . All  thal was  known  about  the gene  was  that  it  had  good  homology  to  the  beta domain  of legume  lectins. That aim of  this  project was  to characterize  the  structure  and  function  of  the  Iectin  protein  using  CD spectra and  X-ray  crystallography. A  TDNA  insertion  line  for the  lectin  gene  and  a number  of 35S  over-expression  lines  that  had  varying  levels  of expression had been generated, but none of these showed any obvious  phenotype. Two protein bands were observed on  Comassie stained SDS-PAGE gels  in  the over-expression  lines and  in MJ  induced wild-type  (WT) . The  two protein bands represented  two  isoforms of  the  lectin 3.1  protein ; in  a glycsylation assay the  larger protein  band was shown  to be heavily glycosylated . A nematode (M. incognita) disease assay djscovered  that the  lectin over-expression lines  had  less  nematode  eggs  compared  to  that  of the WT and  that  the  insertion  line  had  more nematode  eggs  than  the WT. This  data  provides  evidence  that   lectin  3. 1  improves. plant  resistance  against M. incognita infection.  interestingly,  the nematode gut  lining  contains  fucose with  which  Iectin  3.1 binds  to. Keywords: Arabidopsis  thaliana,  lectin’s structure and  function,  pathogen resistance